ANALISIS PENGARUH PROFITABILITAS, REPUTASI AUDITOR, DAN UKURAN PERUSAHAAN TERHADAP PERILAKU INCOME SMOOTHING - Akmal Firdaus; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
This study aims to analyze and examine empirically the factors that affect income smoothing behavior among infrastructure and property companies listed on the Indonesia Stock Exchange. Factors tested in this study are profitability, auditor reputation, and firm size. Sampling method in this research used purposive sampling conducted on infrastructure and property companies listed on the Indonesia Stock Exchange in the period 2009-2013. The hypotheses were tested using a multiple regressions to examine the influence of profitability, auditor reputation, and firm size toward income smoothing behavior. The result of this study shows that profitability, auditor reputation, and firm size have significant influence to income smoothing behavior simultaneously. The  result  of  this  study  also  shows  that  profitability  and  auditor  reputation  have  partially significant influence to income smoothing behavior, but firm size has not partially significant influence to income smoothing behavior.